Beef Price Volatility in Indonesia: Before, During, and After the COVID-19 Pandemic - Atikah Fajriyah Mubarok; Komalawati; Setiadi, Agus (Universitas Muhammadiyah Yogyakarta, 2025)
Indonesia’s beef market has long exhibited structural volatility, which became more pronounced during major disruptions such as COVID-19. Analyzing these fluctuations across different periods is crucial for strengthening market resilience. This paper examines beef price volatility in Indonesia across three critical periods, before the pandemic (2017–2019), during the COVID-19 pandemic (March 2020 – June 2023), and after the pandemic (June 2023 onward), and identifies the key factors influencing it. Daily price data for beef, chicken meat, and eggs were obtained from the Indonesian Strategic Food Price Information Center (PIHPS) for 2017–2024 and analyzed using the GARCH (1,1) model and logarithmic regression with crisis dummy variables. The results show that beef price volatility increased significantly during the pandemic and remained high in the new normal period, confirming the long-term persistence of price shocks. Significant influencing factors include the COVID-19 pandemic, seasonal events (Ramadan and Eid al-Fitr), the price and volatility of chicken meat, and lagged beef imports from previous periods. The methodological contribution of this study lies in the use of daily data and a time-lag structure that captures short-term dynamics more accurately. These results underscore the need for structural reform, daily price monitoring systems, and adaptive market intervention to strengthen Indonesia’s food security and market resilience.